Comprehensive Neonatal Screening for Genetic Disorders in Tribal Populations of Central India - Rakesh K. Jha; Meghali Kaple; Ranjit S. Ambad; Archana Dhok; Ashsish Anjankar (Journal of Pharmacy and Bioallied Sciences)
Background: : Genetic disorders, including sickle cell disease (SCD), thalassemia, and glucose-6-phosphate dehydrogenase (G6PD) deficiency, pose significant health challenges in central India, especially among tribal populations. Comprehensive neonatal screening is crucial for early diagnosis and management. Aim and Objective: This study aims to evaluate the prevalence of SCD, thalassemia, and G6PD deficiency in newborns from tribal regions of central India and assess the impact of comprehensive neonatal screening programs. Materials and Methods: A total of 382 newborns were screened for SCD and thalassemia using high-performance liquid chromatography (HPLC) and for G6PD deficiency using a colorimetric assay. Demographic data were collected, and statistical analyses were performed. Results: The screening identified 28 cases of Sickle cell disease (SCD) (7.3%), 35 cases of thalassemia (9.1%), and 34 cases of G6PD deficiency (8.9%). The study found a significant relationship between maternal education and the prevalence of genetic disorders. Conclusion: The findings highlight the importance of implementing comprehensive neonatal screening programs in tribal populations to improve early detection and management of genetic disorders.